Perceptions of preparedness and intimate partner violence screening practices amongst hand therapists. (December 2018) - Sivagurunathan, Marudan; Packham, Tara; Dimopoulos, Lindsay; Murray, Robyn; Madden, Kim; Bhandari, Mohit; MacDermid, Joy C
Introduction: While hand injuries are reported as common sequelae of intimate partner violence, there is limited attention to hand therapist's screening practices and perceived preparedness to deal with intimate partner violence in hand therapy setting. The primary aim of the current study is to describe the intimate partner violence training, knowledge of referrals, perceived preparedness, and screening practices of hand therapists. Methods: An online survey investigating the perceptions regarding issues pertaining to intimate partner violence was completed by a sample of 189 hand therapists. Areas addressed included intimate partner violence training, perceived preparedness to deal with intimate partner violence-related responsibilities, screening practices and knowledge of resources for referrals. Data were analyzed using descriptive statistics while comparisons of groups used non-parametric analyses to evaluate the impact of training, intimate partner violence experience and knowledge of referrals on preparedness and screening practices. Results: Hand therapists reported low perceived preparedness scores (median = 2.1/7) and screening practices. The majority (73%) of hand therapists indicated having received no intimate partner violence training. Additionally, intimate partner violence training, intimate partner violence experience, and knowledge of referrals had significant impact on hand therapists' perceived preparedness and screening practices. Conclusion: Training is significantly related to perceived preparedness and screening practices. Intimate partner violence screening may result in clients receiving appropriate referrals leading to improved quality of life. Future research should seek out ideal methods for offering intimate partner violence training for hand therapists so that they can meet the needs of clients with intimate partner violence experience.